1982
DOI: 10.1111/j.1365-2125.1982.tb01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of beta‐adrenoceptor blockers under maximal exercise (pindolol v metoprolol v atenolol).

Abstract: 1 The time-related, comparative 3-adrenoceptor blocking effect of metoprolol 150 mg twice daily, atenolol 100mg once daily and pindolol 7.5 mg twice daily on heart rate, blood pressure, work performance, blood lactate, free fatty acids and plasma catecholamines was studied in ten males aged 19-25 years by means of repeated maximal bicycle exercise tests. 2 At steady state several differences in effects were noted among the drugs. These could be explained by differences in P3-selectivity, potency of the chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…However, the changes are modulated by the workload and the mode of exercise. The highly conflicting results from other studies with respect to the influence of beta blockade on catecholamines during exercise [7,[9][10][11]16] may therefore be explained by differences in technique and test models (type of exercise and degree of physical exercise) as well as differences in analytical methods of studying catecholamines.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…However, the changes are modulated by the workload and the mode of exercise. The highly conflicting results from other studies with respect to the influence of beta blockade on catecholamines during exercise [7,[9][10][11]16] may therefore be explained by differences in technique and test models (type of exercise and degree of physical exercise) as well as differences in analytical methods of studying catecholamines.…”
Section: Discussionmentioning
confidence: 59%
“…As shown in this and previous studies [2,4,7,10,11,16], maximal exercise is a potent stimulus for the release of hormones of the adrenocortical axis and from the peripheral neuromotor system. Although maximal performance and the duration of exercise were comparable during intermittent, and continuous exercise, there were marked differences in hormonal responses between the two modes of exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that oxyfedrine has 240 a dual action on the heart and vascular system similar to the effects of nitroglycerine (Parratt & 220 MacKenzie, 1981). In experimental animals it -200 produces marked increase in coronary blood E flow due to arteriolar dilatation, a fall in the left n 180 atrial pressure and peripheral venodilation ' 160 (Parratt, 1974;Parratt & Mackenzie, 1981 is unlikely to explain all the actions of oxyfedrine, since pindolol, a drug with marked intrinsic sympathomimetic activity, does not result in maintenance of double product at angina threshold or peak exercise when compared with placebo (Erikssen et al, 1982).…”
Section: Work Performedmentioning
confidence: 99%